Efforts to Improve Students' Cognitive Abilities by Using the Market Place Activity Model in P5PPRA Activities - Saifullah (Barkah Publishing, 2024)
Based on the researcher's observations as an Islamic Religious Education teacher, especially in class X-A, in Islamic Religious Education learning, teachers tend to use the lecture method so that Islamic Religious Education learning is verbalistic which results in students' activities tending to be passive, only taking notes and listening to the teacher's explanation, resulting in low learning outcomes in Islamic Religious Education subjects. This is evident from the results of the tests that have been carried out, many students still get scores below the KKM. One of the objectives of this study is to determine the application of the Market Place Activity learning model in class X-A at SMA Negeri 1 Kaway XVI, West Aceh Regency, in the 2023/2024 Academic Year. This study uses action research as many as three cycles. Each round consists of four stages, namely: design, action and observation, reflection and revision. The target of this study was class X-A students of SMA Negeri 1 Kaway XVI, West Aceh Regency, Aceh Province, totaling 15 students in the 2023/2024 Academic Year. The data obtained were in the form of test results, observation sheets of student learning activities. Based on the results of this study, it can be concluded that the average value of student learning outcomes during the implementation of the teaching and learning process using the Market Place Activity model was obtained in cycle I, namely 54% and in cycle II, namely 65% ​​and in cycle III students obtained a value of 92%, in cycle III the students' classical learning completeness has been achieved.